Tax Obligations and Financial Performance of Listed Manufacturing Firms in Nigeria - Adu , Cecilia Adurayemi; Oguntuase , Alexander Tunde; Williams, Adekunle Christopher (Indonesian Journal of Banking and Financial Technology, 2024)
The study examined the impact of tax on the financial performance of some listed manufacturing companies in Nigeria. A simple panel and linear regression were used to analyse the data collected through secondary source. It was found out from the results of the regression analysis that probability value of the independent variable as (0.0001) is less than 5% significance level that tax had significant impact on the investment of manufacturing firms likewise tax has significant impact on the profitability of manufacturing firms. It was recommended that the government should ensure they make tax policies that would favour the manufacturing firms and not force them out of businesses which would also affect the economy as a whole.